Second Chance Motherhood : The Pause Button, Not the Stop - Abdel - Kader, Menna (Giza, Egypt Dar Alqahera Alyoum, 2023)
Hey there, new moms! Ever felt like you're drowing in a sea of diapers and baby bottles, your passions buried beneath motherhood's daily chaos? Fear not, for this book is your secret weapon to reignite those lost flames! Inside, you'll uncover guides and exercises that'll rekindle your passions and reclaim your true self. So, remember, motherhood isn't the end, it's just a pause button. Get ready to dive in and let your vibrant, rekindled self shine!
Keywords: Motherhood; Mothers